Different ommochrome pigment mixtures enable sexually dimorphic Batesian mimicry in disjunct populations of the common palmfly butterfly, Elymnias hypermnestra. - Silvio Panettieri; Erisa Gjinaj; George John; David J Lohman (PLoS ONE, 2018)
With varied, brightly patterned wings, butterflies have been the focus of much work on the evolution and development of phenotypic novelty. However, the chemical structures of wing pigments from few butterfly species have been identified. We characterized the orange wing pigments of female Elymnias hypermnestra butterflies (Lepidoptera: Nymphalidae: Satyrinae) from two Southeast Asian populations. This species is a sexually dimorphic Batesian mimic of several model species. Females are polymorphic: in some populations, females are dark, resemble conspecific males, and mimic Euploea spp. In other populations, females differ from males and mimic orange Danaus spp. Using LC-MS/MS, we identified nine ommochrome pigments: six from a population in Chiang Mai, Thailand, and five compounds from a population in Bali, Indonesia. Two ommochromes were found in both populations, and only two of the nine compounds have been previously reported. The sexually dimorphic Thai and Balinese populations are separated spatially by monomorphic populations in peninsular Malaysia, Singapore, and Sumatra, suggesting independent evolution of mimetic female wing pigments in these disjunct populations. These results indicate that other butterfly wing pigments remain to be discovered.